Goods & Service Tax (GST) In India -An Overview, Challenges and Way Out - Aggarwal, Vimal K (Gyan Management Journal, 2010)
In simple words "GST is a tax on goods and services with comprehensive and continuous chain of setoff benefits from the producer’s point and service provider’s point up to the retailer’s level". In continuity with the former Union Finance Minister Mr. P. Chidambaram’s indication in his Budget speech in 2006 that the country will have Goods and Service Tax (GST) regime in 2010, Central Govt. has released first discussion paper on GST. This article focuses on salient features of the proposed GST model, how this tax system will work and highlights the problems likely to be faced by the Central Government while introducing this tax.